Carbon Nanotube‐Silicone Rubber on Active Thin‐Film Implants. Issue 15 (3rd July 2018) - Behrens, Ailke; Foremny, Katharina; Doll, Theodor
Abstract : To improve interfacing with neurites, flexible electrode materials consisting of carbon nanotubes (CNTs) and silicone rubber are investigated. Here, the authors present a method for defined application of CNT‐silicone rubber on electrode surfaces. However, for low impedance as well as intimate contact between nerve cells and electrodes, additional reduction of the silicone rubber layer via etching at the interface is necessary. This requires protection of the electrodes using photoresist. The etching methods are optimized for application on ready‐to‐use electrode arrays and characterized using impedance spectroscopy and scanning electron microscopy. Abstract : Neuronal electrode contact surfaces are improved using a carbon nanotube (CNT) silicone rubber compound. This paper presents a new method for defined application of the flexible electrode material onto electrode surfaces with different diameters (300–500 µm). Wet etching techniques are optimized for such small and thin CNT silicone rubber pads and to ensure the electrode itself stays undamaged by the process. Success is examined using impedance measurements and scanning electron microscopy.